If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 + -1x = 0.25 Solving 50 + -1x = 0.25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50' to each side of the equation. 50 + -50 + -1x = 0.25 + -50 Combine like terms: 50 + -50 = 0 0 + -1x = 0.25 + -50 -1x = 0.25 + -50 Combine like terms: 0.25 + -50 = -49.75 -1x = -49.75 Divide each side by '-1'. x = 49.75 Simplifying x = 49.75
| 2-4a=7a+68 | | 2m-7=-13+4m | | -5b+2=6b-108 | | -7x+5=17-3x | | -5-7m=5m+127 | | 6n+9=-3+2n | | 2t+10=4t+14 | | 6x+5=2x-43 | | 1-7a=6a-142 | | -3w+2=-10-2w | | 3x+5=-7x-15 | | 6m-10=89-3m | | -6t+2=t+86 | | -5x+8=-16+3x | | -2x+4=5x+4 | | 7k+4=-6k-113 | | 6d+3=4d+17 | | 4-n=5n-14 | | 8+2m=m+8 | | w-9=19-3w | | k-8=7k-20 | | 3m+2=122-7m | | -6w+8=-7w+13 | | -3m+7=-89+5m | | t+2=6t-43 | | 2x+8=48+6x | | 2+2*0= | | |3x-6|=7+|x-2| | | 5b+10=b+42 | | 2d-6=-2d+30 | | 7b-10=3b+38 | | -6-2x=x+6 |